A facile way to obtain near-infrared room-temperature phosphorescent soft materials based on Bodipy dyes. Issue 2 (25th November 2019) - Zhang, Ting; Ma, Xiang; Tian, He
Abstract : Near-infrared room-temperature phosphorescence was achieved by employing iodine substituted Bodipy into amorphous polymers. The self-healable gels were also obtained with the incorporation of a crosslinker and quadruple hydrogen bond based moieties. Abstract : Research on pure organic room-temperature phosphorescent (RTP) materials has made great advances but near-infrared (NIR) RTP emitting materials are still rare. Novel amorphous acrylamide copolymers containing iodine substituted borondipyrromethene (Bodipy) were prepared to obtain strong absorption in the visible region and moderate RTP in the NIR region with much larger Stokes shift than the fluorescence emission of traditional Bodipy dyes. Expensive metals and crystallization were left out to avoid biotoxicity and strict preparation conditions. Monoiodo and diiodo-Bodipy derivatives were both designed to study the substitution effect of iodine atoms. Photophysical properties, phosphorescence quantum yield and lifetime were characterized. Gels with NIR RTP emission were facilely prepared with the incorporation of ureidopyrimidone (UPy) and N, N ′-methylenebisacrylamide (MBAA). The mechanical properties of the gels were measured using a rheometer and the results showed that the gels displayed fast self-healing ability due to the strong quadruple hydrogen bonding between UPy moieties.